Relative bioavailability and pharmacokinetic comparison of a fixed‐dose combination tablet of mosapride, pancreatin, and simethicone relative to single‐component mosapride tablets in healthy Mexican subjects - Camarillo Cárdenas, Karen Paola; García González, Jessica; Argüelles Tello, Federico Alberto; Ocampo Ramírez, Jorge Arturo; Moreno Hernández, José Belisario; Pendela, Murali Mohan (Fundamental & clinical pharmacology, 2022)
Abbott Laboratories de México S.A. de C.V. developed a new fixed‐dose combination of mosapride 5 mg, pancreatin 170 mg, and simethicone 125 mg as an alternative to the mosapride monotherapy to improve overall satisfaction and adequate relief of gastrointestinal disorders symptoms and to reduce multiple pill burden. As a part of the fixed‐dose combination registration process in Mexico, a pharmacokinetic and relative bioavailability study was carried out to demonstrate nonexistence of pharmacokinetic interaction when mosapride is administered alone or in combination with pancreatin and simethicone using DOSIER® (mosapride) 5‐mg tablets as a reference product. Tolerability of the fixed‐dose combination tablet was assessed. In this open‐label, randomized, oral single‐dose, two‐way crossover study, 65 healthy male and female subjects received either the fixed‐dose combination tablet or the reference product during each study period. The two study periods were separated by a 7‐day washout period. Mosapride concentrations in plasma samples were determined using a validated ultra‐performance liquid chromatography coupled with tandem mass spectrometry (UPLC‐MS/MS) method. Blood samples were collected for up to 16 h post dose. The primary evaluation criteria were Cmax and AUC0–t for mosapride. The 90% confidence intervals for the ratio of geometric means for Cmax (96.12% to 110.90%) and AUC0–t (99.07% to 108.06%) were within the defined acceptance limits of 75% to 133% and 80% to 125% for Cmax and AUC0–t, respectively, indicating bioequivalence between the two products. Both products were safe and well tolerated. Therefore, mosapride in combination with pancreatin and simethicone tablet is bioequivalent to mosapride alone, and no new safety signals emerged.